2014
DOI: 10.1111/jzo.12109
|View full text |Cite
|
Sign up to set email alerts
|

The role of the neck in the feeding behaviour of the Tyrannosauridae: inference based on kinematics and muscle function of extant avians

Abstract: Tyrannosaurid necks were strong and powerful instruments for wielding the jaws during feeding. Hypotheses of tyrannosaurid neck function are here grounded by observations of neck morphology and function in extant archosaurs. Respectively derived morphologies in birds, crocodilians and tyrannosaurids compromise inferences for some muscles. However, alternate reconstructions indicate that tyrannosaurid neck muscles combined the robustness of crocodilian musculature with the functional regionalization seen in bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
(121 reference statements)
1
29
0
Order By: Relevance
“…For example, the occiput of Hatzegopteryx shows obvious signs of substantial soft-tissue attachment: the nuchal line is well developed and long, and its dorsolateral edges are deeply dished and marked with vertical scarring (Buffetaut, Grigorescu & Csiki, 2002; Buffetaut, Grigorescu & Csiki, 2003). Comparison with extant reptile anatomy Herrel & De Vree, 1999; Cleuren & De Vree, 2000; Tsuihiji, 2005; Tsuihiji, 2010; Snively & Russell, 2007; Snively et al, 2014 suggests that these features reflect large insertion areas for transversospinalis musculature (specifically m. transversospinalis capiti and the m. epistropheo-capitis/splenius group), cervical musculature devoted to head and neck extension and lateral flexion. The large neural spines on posterior azhdarchid cervicals and anterior thoracic vertebrae provide potential origin sites for m. transversospinalis capiti, while the long neural spine of cervical III likely anchored m. epistropheo-capitis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the occiput of Hatzegopteryx shows obvious signs of substantial soft-tissue attachment: the nuchal line is well developed and long, and its dorsolateral edges are deeply dished and marked with vertical scarring (Buffetaut, Grigorescu & Csiki, 2002; Buffetaut, Grigorescu & Csiki, 2003). Comparison with extant reptile anatomy Herrel & De Vree, 1999; Cleuren & De Vree, 2000; Tsuihiji, 2005; Tsuihiji, 2010; Snively & Russell, 2007; Snively et al, 2014 suggests that these features reflect large insertion areas for transversospinalis musculature (specifically m. transversospinalis capiti and the m. epistropheo-capitis/splenius group), cervical musculature devoted to head and neck extension and lateral flexion. The large neural spines on posterior azhdarchid cervicals and anterior thoracic vertebrae provide potential origin sites for m. transversospinalis capiti, while the long neural spine of cervical III likely anchored m. epistropheo-capitis.…”
Section: Resultsmentioning
confidence: 99%
“…Specific discussion : From electromyographic studies in the chicken ( Gallus gallus domesticus ) it was found that the M. complexus is involved in lateroflexion, dorsiflexion and rolling of the head [ 32 ]. The arrangement of the muscle in T .…”
Section: Results and Muscle Specific Discussionmentioning
confidence: 99%
“…This sulcus can also often be seen quite commonly in non-avian dinosaurs up to the condition in Tyrannosauroidea, while its absence is a derived trait of coelurosaurs closer to birds. For example, a shallow sulcus on the anteromedial edge of the scapular blade is apparent on the scapula of Ceratosaurus dentisulcatus (UMNH VP 5278), Megalosaurus bucklandii (Walker, 1964) (Snively and Russell, 2007;Snively et al, 2014).…”
Section: Trapezius (Level I)mentioning
confidence: 99%